Rhabdomyolysis in water buffaloes (Bubalus bubalis) - Llada, Ignacio; Gianechini, Leonor S.; Odriozola, Ernesto; Brambilla, Emilio; Fernández, Eduardo; Scioli, Valeria; Cantón, Germán; Morrell, Eleonora (Brazilian Journal of Veterinary Pathology, 2019)
Rhabdomyolysis is a myopathy characterized by severe acute myonecrosis with lysis of muscle cells and extravasation of its content into the bloodstream, causing a secondary renal failure and myoglobinuria. Case-reports have been documented in a wide range of wild or domestic animal species, but to our knowledge, no reports in water buffaloes (Bubalus bubalis) have been done. Three animals had signs of paralysis, muscle tremors and myoglobinuria while others died spontaneously. Samples of blood from affected animals showed increased levels of creatin kinase (CK), potassium (K), aspartate transaminase (AST), and lactate dehydrogenase (LDH). In addition, Selenium (Se) levels of those animals were low. Necropsy findings consisted of severe gelatinous and yellowish edema and pallor of the skeletal muscles of the hind limbs, lumbar, cervical and scapular region. Microscopically, acute and severe segmental monophasic coagulative necrosis of skeletal muscles and acute pigmentary tubular nephrosis was observed. We suspect that selenium deficiency was a predisposing factor of rhabdomyolysis in this particular case.